APLIKASI ELECTRONIC SIGNATURE (eSign) DENGAN QR-CODE PADA PROGRAM STUDI TEKNIK INFORMATIKA UMJ BERBASIS WEB - Zein, Risa Azzahra; Meilina, Popy; Dores, Ardiansyah; Ambo, Sitti Nurbaya (Jurnal Sistem Informasi, Teknologi Informatika dan Komputer, 2025)
Currently, the use of electronic signature is something that is often done, including in the academic realm at universities. The use of electronic signatures in the Informatics Engineering Study Program at Muhammadiyah University of Jakarta is still not computerized, starting from the application process it is still carried out on various platforms and the signing process uses separate software so there is no system or application that can be used. organize the process. The aim of designing this electronic signature application is to facilitate the electronic signing process within the scope of the Information Engineering Study Program, Muhammadiyah University of Jakarta, so that the submission and signing process can be carried out quickly in one application and the authenticity of the signature on which the document is signed can be proven to be genuine. The data collection methods used were literature studies, interviews and observations. The development method used is the Waterfall Method, where software development follows linear and sequential steps, thereby creating a structured and organized approach. Testing of the electronic signature application is carried out by carrying out black box testing and after testing it can be concluded that the application can run well and the electronic signature process can be more effective and efficient. Keywords: electronic signature, Waterfall Method, application, effective and efficient